Partycypacja lokalnej społeczności w kształtowaniu procesu rozwojowego w gminie - Marta Szaja (Ekonomiczne Problemy Usług, 2015)
Community participation is commonly defined as a process by which citizens act in response to public concerns, voice their opinions about decisions that affect them, and take responsibility for changes to their community and commune. Research path taken in this work is concentrate around community participation and its impact on the process of converting local functional structures. General aim of this study is to attempt to ascertain the actual level of local community involvement in the commune development process.